2009
DOI: 10.1002/zaac.200900175
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Metal Distances at the Limit: Cr–Cr 1.73 Å – the Importance of the Ligand and its Fine Tuning

Abstract: The synthesis and structure of a homobimetallic chromium complex is reported. The ligand used to stabilise the quintuply bonded metals is a sterically fine‐tuned guanidinate. A chromium–chromium bond length of 1.7293(12) Å was observed. It is the shortest metal–metal distance reported for a stable compound yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 21 publications
4
64
0
2
Order By: Relevance
“…In 2005, Power et al [86] reported the synthesis of the first isolable formal quintuply bonded (σ 2 π 4 δ 4 ) dichromium complex ArCrCrAr (Ar = 2,6-(2,6-iPr 2 C 6 H 3 ) 2 C 6 H 3 ) with an unusually short Cr-Cr distance (1.835 Å). This report stimulated several theoretical and experimental studies [87][88][89][90][91][92][93][94][95] in which the nature of the Cr-Cr bond was probed. Since then, several complexes featuring ultra-short Cr-Cr bonds of around 1.75 Å have been identified [88][89][90][94][95][96].…”
Section: High Bond Orders In Transition Metalssupporting
confidence: 56%
See 1 more Smart Citation
“…In 2005, Power et al [86] reported the synthesis of the first isolable formal quintuply bonded (σ 2 π 4 δ 4 ) dichromium complex ArCrCrAr (Ar = 2,6-(2,6-iPr 2 C 6 H 3 ) 2 C 6 H 3 ) with an unusually short Cr-Cr distance (1.835 Å). This report stimulated several theoretical and experimental studies [87][88][89][90][91][92][93][94][95] in which the nature of the Cr-Cr bond was probed. Since then, several complexes featuring ultra-short Cr-Cr bonds of around 1.75 Å have been identified [88][89][90][94][95][96].…”
Section: High Bond Orders In Transition Metalssupporting
confidence: 56%
“…Since then, several complexes featuring ultra-short Cr-Cr bonds of around 1.75 Å have been identified [88][89][90][94][95][96]. The shortest Cr-Cr distance (1.729 Å) to date has been observed by Noor et al [95].…”
Section: High Bond Orders In Transition Metalsmentioning
confidence: 97%
“…[60,61] Even most of the recently described dinuclear chromium complexes with a quintuple bond follow, in principle, this concept of the stabilization of dinuclear complexes by L = ABC. [62][63][64] Sasols PNP ligands, [7] as typical L = ABC ligands, are the best for selective tetramerization but not totally exclusive. A very small number of exceptions exist with L = ABCD, giving some 1-octene selectivity like PNNP [7] and PCCP.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…We also made an effort to synthesize a com pound containing a Cr-Cr bond similar to diazadi ene and amidinate derivatives containing the chromi um-chromium quintuple bond synthesized recently. [34][35][36][37][38][39][40][41] Results and Discussion Synthesis and characterization of compounds 2, 4-8, and 10. The replacement of CO groups by dpp bian in chromium hexacarbonyl requires the presence of an ex cess of the latter (2-4 moles of dpp bian per mole of Cr(CO) 6 ), the prolonged heating of the reaction mixture (20 h at 80 C), and the removal from time to time of carbon monoxide that formed.…”
mentioning
confidence: 99%
“…Zr-C(38) 2.4802(19) N(1)-Zr-N(2) 87.94(6) Zr-C(39) 2.507(2) N(1)-Zr-Cl 109.53(4) Zr-C(40) 2.520(2) N(2)-Zr-Cl 113.90(4) Zr-C(41) 2.498(2)…”
unclassified